DISOLUSI ASAM MEFENAMAT DALAM SISTEM DISPERSI PADAT DENGAN PEG 4000 - Yulias Ninik Windriyati; Sugiyono Sugiyono; Lies Sunarliawati (Universitas Wahid Hasyim Semarang, 2014)
ABSTRACTMefenamic acid is an analgetic that insoluble in water and classified into class II in theBiopharmaceutic Classification System (BCS), therefore the dissolution become the rate limitingstep of absorption process and bioavailability. Several approaches are required to improve thedissolution like preparation of solid dispersion. The aim of this research is to know the dissolutionof mefenamic acid in solid dispersion system with PEG 4000.Solid dispersion of mefenamic acid-PEG 4000 were prepared by fusion method withcontain PEG 4000 for FI (20%), FII (40%), FIII(60%), FIV (80%) and FV (100%) respectivelywere compared with the weight of mefenamic acid. The powder of solid dispersion systems wereinvestigated for its recovery and dissolution in medium fosfat buffer pH 7.4 until 60 minutes. Puremefenamic acid and the physical mixture with polimer were used as compared powders. Theresult of dissolution testing were revealed by Dissolution Efficiency (DE60)The result showed that PEG 4000 can increased the dissolution of mefenamic acid fromsolid dispersion systems. The DE60 of mefenamic acid-PEG 4000 from FI 30,41%; FII 30,60%;FIII 36,19%; FIV 36,42%; FV 41,92%; and the physical mixture of FV 23,63% respectively. Thevariations of concentration of PEG 4000 in this solid dispersion not influence the dissolution ofmefenamic acidKeywords : Mefenamic acid, PEG 6000, PVP, solid dispersion, dissolution